The role of blockchain technology in ensuring security and immutability of open data in healthcare - Guimarães, Tiago André Saraiva (2023)
Clinical information is highly confidential due to its sensitive nature. Implementing health information systems has raised concerns regarding in teroperability, privacy, and security. The storage and retrieval of this infor mation also present the same problems. Therefore, any effort to introduce healthcare information systems must ensure patient data's safety, privacy, integ rity, and immutability. Blockchain technology and the openEHR open data model have emerged to address these concerns, providing a solution that guar antees data security, interoperability between systems, and the accuracy of stored data queries. Two different architectures were developed and subjected to several performance tests to enhance security and immutability in open data models implemented in healthcare institutions. The results were analysed to de termine which architecture provides more value to a healthcare institution. Sub sequently, a discussion was held to draw appropriate conclusions.